Spatial distribution and prognostic value of T cell subtypes and immune biomarkers in p16-negative HNSCC - Krum, David Maximilian; Rösch, Saskia; Warta, Rolf; Mogler, Carolin; Yılmaz Topçuoğlu, Miray-Su; Grabe, Niels; Schuler, Patrick; Dyckhoff, Gerhard; Herold-Mende, Christel (Cells, 2025)
Patients with head and neck squamous cell carcinoma (HNSCC) suffer from severe morbidity and mortality. Immunotherapy represents a novel promising treatment option. Therefore, a better understanding of the immune niche is needed. This study focuses on the spatial distribution and prognostic value of different T cell subtypes in 84 HNSCC specimens as well as chemokine and cytokine levels associated with spatial T cell infiltration. Density of T helper (TH), cytotoxic (CTL), and regulatory T cells (Treg) was quantified by multicolor tissue cytometry on a single cell level in whole tissue sections, discriminating between T cells located in epithelial tumor cell nests or tumor stroma, respectively. In addition, quantitative levels of 27 immune-related factors were assessed. Survival analysis of patients with p16-negative HNSCC revealed higher stromal Treg densities to be an independent prognostic factor for better progression-free and overall survival. Furthermore, high levels of CXCL10, IL-9, and CCL4 were associated with significantly higher numbers of T cells, especially for CTL with direct contact to tumor cells, whereas for VEGF the opposite effect was observed in the tumor stroma. In conclusion, Treg cell infiltration as well as distinct cytokine levels could serve as new immune biomarkers in p16-negative HNSCC to predict survival and the spatial distribution of T cells.
Veröffentlicht: 27. Mai 2025
Gesehen am 16.10.2025